Empirical study on the construction of a cognitive model of factorization in eighth-grade students - Zhangtao, Xu; Jiabao, Cai; Jiale, Li; Na, Li; Bo, Li (Frontiers in Psychology, 2023)
The construction of cognitive models is the basis for cognitive diagnosis, and the cognitive models will change based on the purpose of the study. According to the purpose of mathematical education, the factorization cognitive model is constructed based on the competence dimension and the knowledge dimension. The factorization cognitive model was preliminarily constructed using expert-defined and literature surveys, and a small-scale test was subsequently carried out. The rationality of the cognitive model was tested through verbal reports and the regression of the item’s difficulty on the cognitive attributes. There are 72 students from two classes in the 8th grade of a junior high school in Wuhan as study samples. A diagnosis would be made based on the mastery of factorization knowledge and the level of mathematical operation ability of the eighth graders by the cognitive model. Research 1 demonstrates that the construction of the factorization cognitive model is reasonable. Research 2 shows that about 79% of students’ mathematics operation ability can reach the level of knowledge-understanding, 71% of students can reach the level of knowledge-transfer, and only 28% of students can reach the level of knowledge- innovation.